Molecular clock as insight to estimate the evolutionary history and times of divergence for 10 nominal astyanax species (Characiformes, characidae): An evolutionary approach in species with 2n = 36, 46, 48, and 50 chromosomes - Piscor, Diovani [UNESP]; Pozzobon, Allan Pierre Bonetti; Fernandes, Carlos Alexandre; Centofante, Liano; Parise-Maltempi, Patricia Pasquali [UNESP] (SAGE Publications, 2019)
Astyanax is a genus with a wide distribution ranging from the south United States to north of Patagonia (Argentina). The available cytogenetic data on Astyanax indicate a high karyotypic diversity, with diploid number of 36-52 chromosomes, presence of B chromosomes, heterochromatin polymorphism, and variations with respect to the number and localization of nucleolar organizer regions (NORs) and 18S and 5S ribosomal DNA sites. In the present study, we estimated the evolutionary history and times of divergence for 10 nominal Astyanax species from the South and Central/North American (Cna) continents, which present distinct chromosomal characteristics, based on molecular clocks inferred from mitochondrial DNA sequence. The molecular clock results indicate the origin of three distinct clades (Humeral dark spot [Hds]; Diffuse humeral spot [Dhs]; Cna group) during the late Miocene about 11.2 million years ago (Mya). Thus, Astyanax mexicanus (Cna) represent a species that diverged a long time ago (∼8.6 Mya) from the Hds group, and Astyanax schubarti is the oldest species (∼6.5 Mya) among the Dhs species.
Keywords: chromomycin A 3; chromosomal evolution; COI; phylogenetic analysis; rDNA